Rabbit meat contribution to vulnerable family diet, in Mendoza northeastern departments, Argentina - Quagliariello, Roxana Gaby; Lafalla Manzano, Laura Patricia (World Rabbit Science Association, 2021)
Ponencia y Poster. En Actas del Congreso, el trabajo figura: Quagliariello G., Lafalla L. - Importance of the contribution of rabbit meat in the diet of families in vulnerable conditions, in departments of northeastern Mendoza, Argentina. O-09